Soil erosion estimation using Erosion Potential Method in the Vjosa River Basin, Albania - Oltion Marko; Joana Gjipalaj; Dritan Profka; Neritan Shkodrani (AIMS Environmental Science, 2023)
Soil erosion is a major environmental threat to soil sustainability and productivity with knock-on effects on agriculture, climate change, etc. Factors influencing soil erosion are many and usually divided into natural and human causes. Massive deforestation, intensive agriculture, temperature and wind, rainfall intensity, human activities and climate changes are listed as the main causes of soil erosion. Calculation of the coefficient of soil erosion is very important to prevent the event. One of the methods used worldwide to calculate soil loss and the erosion coefficient is the Erosion Potential Method. In this study, 49 sub-basins of the Vjosa River Basin in Albania were evaluated. Results showed that the phenomenon of erosion is present in all sub-basins, varying from 0.01 to 0.71. Thus, the categorization of soil erosion varies from heavy to very slight erosion. Moreover, the overall sediment yield calculated for the Vjosa River Basin was 2326917 m3/year. In conclusion, the application of the Erosion Potential Method is reliable for evaluating erosion and can further be applied in our country's conditions.